Interaction Between The Renin Angiotensin System And A1-Adrenergic Receptors At The Renal Resistance Vessels In Diabetes Mellitus And Hypertension [QP572.A54 A288 2007 f rb]. - Dewa, Aidiahmad (2007)
α1-adrenoseptor dan reseptor subjenis angiotensin jenis 1 (AT1) memainkan peranan penting dalam pengawalaturan hemodinamik ginjal pada peringkat vaskulatur rintangan ginjal.